Macroeconomic Shifts in Indonesia: Analyzing the Impact of The United States (US) – China Trade War - Nora Ria Retnasih; Putri Eliza Syahda (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan)
The trade war between the United States and China has created global trade tensions that have had a significant impact on the economies of various countries, including Indonesia. This study analyzes the effects of the trade war, represented by the Trade Tension Index and Import Tariff variables, on Indonesia's macro economy during the 2018–2023 period using monthly data. The macroeconomic variables analyzed include inflation, exports, imports, exchange rates, and industrial production indices. The VECM method is used to evaluate the short-term and long-term effects of the trade war on these variables. The results show that the trade war have a significant effect, both in the short and long term, on inflation, exports, imports, and exchange rates. However, the effect on the industrial production index is not significant. These findings indicate that the trade war not only affects Indonesia's price stability and international trade but also has implications for exchange rate volatility, which can complicate the management of monetary and trade policies. The results of this study emphasize the importance of strengthening the resilience of the trade sector and developing adaptive industrial policies to mitigate the negative impacts of trade wars while maximizing opportunities from international trade dynamics.